2013
DOI: 10.36076/ppj.2013/16/251
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Complications Related to Intrathecal Drug Delivery System and Spinal Cord Stimulator System Implantations at a Comprehensive Cancer Pain Center

Abstract: Background: Intrathecal drug delivery (IDD) and spinal cord stimulator (SCS) systems are implantable devices for the management of both chronic and cancer pain. Although these therapies have favorable long-term outcomes, they are associated with occasional complications including infection. The incidence of infectious complications varies from 2 - 8% and frequently requires prolonged antibiotics and device revision or removal. Cancer patients are particularly susceptible to infectious complications because the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Due to the consecutive patient selection design, we negated that our cohort somehow had a lower burden of established risk factors, such as diabetes, poor nutritional status, smoking, use of corticosteroids, chemotherapy, and radiation therapy 18 . A plausible explanation for a low infection rate in our study was the consistent treatment of pre‐operative Staphylococcus aureus colonization and the use of postoperative antibiotic prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the consecutive patient selection design, we negated that our cohort somehow had a lower burden of established risk factors, such as diabetes, poor nutritional status, smoking, use of corticosteroids, chemotherapy, and radiation therapy 18 . A plausible explanation for a low infection rate in our study was the consistent treatment of pre‐operative Staphylococcus aureus colonization and the use of postoperative antibiotic prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown contrary to this belief, the rates of surgical site infection for pain implants are not greater in cancer patients compared to patients without cancer. 19 , 22 However, a study by Hoelzer et al evaluating spinal cord stimulator implants did have a statistically significant decrease in incidence of surgical site infection with use of post-operative antibiotics for 7 days in non-cancer patients. 23 This practice may reflect provider preference based on these findings.…”
Section: Discussionmentioning
confidence: 98%
“… 18 Previous studies have shown that the rate of perioperative infection for implanted pain devices to range from 2.8% to 6%. 19–21 Many IDDS are utilized in cancer patients who may have concomitant immunotherapy and may be immunocompromised. Studies have shown contrary to this belief, the rates of surgical site infection for pain implants are not greater in cancer patients compared to patients without cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 127 In other studies, the incidence of infection in the cancer patient population was 2.7–3.2%. 128 , 129…”
Section: Data Evaluation and Discussionmentioning
confidence: 99%